Dimensional of Pancasila Student Profile in Science Learning PGSD Students - Harlinda Syofyan; Oktian Fajar Nugroho; Ainur Rosyid; Syahrizal Dwi Putra (Universitas Pendidikan Ganesha, 2022)
Character education must be carried out early and continuously to overcome problems such as dishonesty, irresponsibility, not caring about other people or the environment, and so on. Value and character education are needed to balance technological and human development. This study aimed to measure the profile dimensions of Pancasila students in PGSD students in science learning. This type of research is descriptive qualitative. The sample used in this study were all students taking science courses, totaling 67 students. The method used for data collection is a questionnaire—acquisition of data generated from Angke. The instrument used in collecting data is a questionnaire. The data analysis technique used is descriptive qualitative and quantitative analysis. The research results on the dimensions of righteousness to God Almighty are very good. In the second dimension get, 46% for the very good category, while in the good category get, 54%. The third dimension gets 48% for the very good category, while the good category gets 52%. The fourth dimension is 55% for the very good category and 45% for the good category. The fifth dimension gets 12% for the very good category and 88% for the good category. The last dimension, the very good category, gets 16% and 84% for the good category.